Effects of Light Quality on Morphology, Enzyme Activities, and Bioactive Compound Contents in Anoectochilus roxburghii - Ye, Shenyi; Shao, Qingsong; Xu, Mengjie; Li, Shuailing; Wu, Mei; Tan, Xin; Su, Liyang (Frontiers in Plant Science, 2017)
The aim of this study was to investigate the effects of light quality on the morphological traits, leaf anatomical characteristics, antioxidant enzyme (superoxide dismutase, catalase, and peroxidase) activities, photosynthetic pigments content, and bioactive compounds (phenols, flavonoids, and polysaccharides) content in Anoectochilus roxburghii. Plants of A. roxburghii were grown under light filtered through four differently colored films for 8 months. The four treatments were red film (RF), blue film (BF), yellow film (YF), and colorless plastic film (CLF; control, CK). Compared with the A. roxburghii plants in CK, those in the BF treatment showed significantly greater stem diameter, fresh weight, leaf area, stomatal frequency, chlorophyll content (Chl a, Chl b, Chl a+b), antioxidant enzyme activities, and active compound (polysaccharides, flavones) content. The plants in the RF treatment showed the greatest plant height and phenolics contents. These results show that growing A. roxburghii plants under blue film is a useful technique to improve quality. This technique is conducive to achieving large-scale sustainable production of high-quality plant materials.